PENGARUH TUNJANGAN PENGHASILAN PEGAWAI (TPP) TERHADAP KINERJA PEGAWAI PADA DINAS KEPARIWISATAAN KEBUDAYAAN KEPEMUDAAN DAN OLAHRAGA KABUPATEN SUKABUMI - M. Rijal Amirulloh (STISIP Widyapuri Mandiri Sukabumi, 2023)
This study aims to examine the effect of employee income allowance (TPP) on employee performance at the Sukabumi Regency Tourism, Culture, Youth and Sports Office. The research method used is a survey method using a questionnaire as a data collection instrument. The sample taken was employees at the Sukabumi Regency Tourism, Culture, Youth and Sports Office who received TPP. The results showed that there was a significant influence between TPP and employee performance. This indicates that TPP can be one of the factors that influence employee performance. Therefore, the Sukabumi District Tourism, Culture, Youth and Sports Office should consider providing adequate TPP to improve employee performance and the achievement of organizational goals.